The Impact of Task Complexity and Auditor Experience on Audit Judgment Using Auditor Ethics as a Moderating Factor - Nabila Fary Adiyana; Barokah Dina Juniarti (Yayasan Az Zukhruf Cendikia, 2025)
Purpose - This study aims to determine the influence of auditor experience and task complexity on audit judgment with auditor ethics as a moderation variable. Design/methodology/approach - This study uses quantitative data, this research is conducted using questionnaires that are shared individually with auditors via email and social media. Each questionnaire distributed has 30 statements to be answered by respondents. From the statements that were distributed, there were 30 respondents who gave answers. The analysis technique used to test the hypothesis is using PLS SEM Version 3.0. Findings - The results of this study show that the auditor experience variable has a positive and statistically significant effect on audit judgment, the task complexity variable has a negative and statistically insignificant effect on audit judgment, auditor ethics strengthens the relationship between auditor experience and audit judgement and auditor ethics does not strengthen the relationship between task complexity and audit judgment. Research limitations/implications - This research hopes to provide information regarding audit judgment and can provide benefits in decision making and can be used as reference material for further research.